2013
DOI: 10.1371/journal.pone.0074031
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of RIC8A Function in Mouse Neurons Leads to a Severe Neuromuscular Phenotype and Postnatal Death

Abstract: Resistance to inhibitors of cholinesterase 8 (RIC8) is a guanine nucleotide exchange factor required for the intracellular regulation of G protein signalling. RIC8 activates different Gα subunits via non-canonical pathway, thereby amplifying and prolonging the G protein mediated signal. In order to circumvent the embryonic lethality associated with the absence of RIC8A and to study its role in the nervous system, we constructed Ric8a conditional knockout mice using Cre/loxP technology. Introduction of a synaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 43 publications
1
17
0
1
Order By: Relevance
“…Moreover, similarly to the neuron‐specific ablation of RIC8A, the majority of P0 Nes;Ric8a CKO mice had myocardial hypoplasia and thinner myocardium. The myocardial defects were probably due to disturbed innervation as suggested earlier (Ruisu et al, ). In addition, the neural crest cells provide all parasympathetic innervation of the heart that controls the normal myocardial function (Kirby et al, ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Moreover, similarly to the neuron‐specific ablation of RIC8A, the majority of P0 Nes;Ric8a CKO mice had myocardial hypoplasia and thinner myocardium. The myocardial defects were probably due to disturbed innervation as suggested earlier (Ruisu et al, ). In addition, the neural crest cells provide all parasympathetic innervation of the heart that controls the normal myocardial function (Kirby et al, ).…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, a recent study in Drosophila showed that association of neuronal calcium sensor 1 with Ric8a co‐regulates the number of synapses and the probability of neurotransmitter release per synapse (Mansilla et al, ). In our previous study, we also found that RIC8A deficiency in differentiated neurons affects the neuromuscular signaling and the mutants exhibit highly similar phenotype and muscle fiber atrophy as the Nes;Ric8a CKO mice (Ruisu et al, ). These results strongly suggest that RIC8A may have a role in regulating muscle innervation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Conditional gene targeting using a floxed ric8 allele and an hGFAP-cre that targets Ric-8A expression in neural progenitors and astroglia resulted in mice with a disorganized Bergmann glial scaffolding, defective granule cell migration, and disrupted Purkinje cell positioning (22). A synapsin I promoter driven Cre ablated Ric-8A function in most differentiated neuron populations and resulted in early post natal death due to a severe neuromuscular phenotype (23). However, whether the phenotypes that arose in these conditionally ric8 targeted mice resulted from Gα protein deficiency or due to a loss of Ric-8A function in non-canonical G-protein signaling was unexplored in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, AGS3S was found to be expressed endogenously in mammalian heart [7]. Intriguingly, a recent report on Ric-8A knockout mice showed that the loss of Ric-8A results in early postnatal death with abnormal heart beat, heart muscle hypoplasia as well as misplaced sinoatrial node [36]. Mice lacking AGS3 also exhibit altered cardiovascular function [37].…”
Section: Discussionmentioning
confidence: 99%